The Effect of Myrmecodia pendans Ethanol Extract on Blood Vessels Within Pulpitis (Study on Sprague Dawley Rats) - Janti Sudiono; Patricia Revana (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2020)
Sarang semut (Myrmecodia pendans) is one of traditional herbs used to treat various diseases. Myrmecodia pendanscontain chemical compound flavonoid which has anti inflammation effects. Pulpitis is a dental pulp inflammation thatcan be caused by bacteria invasion, physical trauma or iatrogenic factor which affecting blood vessels in dental pulp.This research is an in vivo laboratory experimental pre and post treatment with control. The purpose of this study is tofind out the effects of Myrmecodia pendans ethanol extract on blood vessels appearance of Sprague Dawley rats’dental pulps which had been inducted with 0,01ml Porphyromonas gingivalis for 48 hours. The subjects were dividedinto 3 groups with Group I representing the negative control, group II representing treated group with Myrmecodiapendans ethanol extract, and group III representing positive control with Ca(OH)2. Group II and III were divided intosubgroups based on the treatment periods of 48, 96, 168, 336 hours. The statistic results showed that there weresignificant differences (p<0.05) among the pulpitis, negative control, positive control Ca(OH)2 and the Myrmecodiapendans treatment subgroups of 48, 96, 168, 336 hours. Myrmecodia pendans ethanol extract has comparable antiinflammation effect with Ca(OH)2 which is used to pulpitis commercial medicament.